Knowledge Regarding Glasgow Coma Scale among Nurses Working at Selected Hospitals of Chitwan, Nepal - Sedain, Prativa; Bhusal, Mina Kumari (Journal of College of Medical Sciences-Nepal, 2019)
Background: Glasgow Coma Scale (GCS) refers to the internationally standardized measurement tool used to check the level of consciousness. The objective of this study is to find out the knowledge regarding Glasgow Coma Scale among nurses working in selected Hospital Bharatpur, Chitwan. Methods: A descriptive cross-sectional study design was used with 154 nurses working in the different critical wards by using Non-probability, convenient sampling technique. Data was collected by using structured, self-administered questionnaire Result: Result of this study revealed that mean age of the respondents was 23.24. Majority of the respondents belongs to age group 20-24 years (72.1%), Proficiency Certificate Level Nursing (69.5%), education in private institution (90.9%), staff nurse (89.6%), <12-month experience (58.9%), receive in-service education (57.8%). Only 33.1% of the respondent had good level of knowledge. Likewise, 66.9% respondents had good knowledge regarding eye opening component, 33.0% had good knowledge regarding motor component and 66.2% had good knowledge regarding verbal response of GCS. The significant influencing variable for the level of knowledge are educational institute (p=0.028), availability of protocol on GCS (p=0.048) and habit of self-directed learning (p=0.036). Conclusions: It is concluded that majority of respondents have unsatisfactory level of knowledge regarding GCS. Therefore, knowledge upgrading programs should be conducted through in-service education and training.